POLICIES FOR THE INCLUSION OF PEOPLE WITH DISABILITIES IN “INSTITUTO FEDERAL DO PARANÁ” (Interdisciplinary Studies Journal, 2024)
This article presents a narrative review of the literature about inclusive education policies for people with disabilities in the IFPR. A total of 12 works were consulted, including articles, master's dissertations and doctoral theses indexed in the Brazilian Digital Library of Theses and Dissertations (BDTD) of the Coordination for the Improvement of Higher Education Personnel (CAPES) and in the Scientific Electronic Library Online (Scielo). The discussion was structured considering the quota policies, the School Census indicators, the socio-emotional conditions of this population and in five thematic dimensions in the context of the IFPR. The results found indicate that there is a mismatch between the instituted public policies and what the IFPR has done over the years for the inclusion of students with special educational needs, while proposing a diffuse policy that includes, also neglects or denies the inclusion in a scenario in which some obstacles have already been overcome, although others still need to advance, indicating the need to involve a commitment from all in an education for all.
Keywords: Instituto Federal do Paraná; Inclusive Education; Public Policies for education; Disabled person